La rencontre entre le graffiti et le cinéma dans le film Vandal : vers une création hybride - Olga Stepanova (Itinéraires)
Graffiti is a drawing or inscription drawn on the walls of buildings or other surfaces in the city without permission from the authorities. Often confused with street art, graffiti is first and foremost an illegal activity classified as vandalism by the law. Street art, in turn, is a natural evolution of graffiti, serving aesthetic purposes, aiming at communicating with the public through humor and irony. The filmic graffiti, as a hybrid product, loses some of its original characteristics and takes on a form considerably different from the one found in its original state. In the film Vandal, directed by Hélier Cisterne, it seems to exist independently of its support, occupy the entire diegetic space and look at the viewer. The story the movie tells about graffiti gradually turns into a story that graffiti tells about itself.